Egg-White Proteins Have a Minor Impact on the Bactericidal Action of Egg White Toward Salmonella Enteritidis at 45°C - Baron, Florence; Cochet, Marie-Françoise; Alabdeh, Mariah; Guérin-Dubiard, Catherine; Gautier, Michel; Nau, Françoise; Andrews, Simon C.; Bonnassie, Sylvie; Jan, Sophie (Frontiers in Microbiology, 2020)
Salmonella enterica serovar Enteritidis is noted for its ability to survive the harsh antibacterial activity of egg white which is presumed to explain its occurrence as the major food-borne pathogen associated with the consumption of eggs and egg products. Liquid egg white is a major ingredient for the food industry but, because of its thermal fragility, pasteurization is performed at the modest temperature of 57 °C (for 2 to 6 min). Unfortunately, such treatment does not lead to sufficient reduction in S. Enteritidis contamination, which is a clear health concern when the product is consumed without cooking. However, egg white is able to limit S. Enteritidis growth due to its alkaline pH, iron deficiency and multiple antimicrobial proteins. This anti-Salmonella activity of egg white is temperature dependent and becomes bactericidal once the incubation temperature exceeds 42°C. This property is exploited in highly-promising pasteurization treatment (42-45 °C for 1 to 5 days) which achieves complete killing of S. Enteritidis. However, the precise mechanism and the role of the egg-white proteins are not fully understood. Here, the impact of exposure of S. Enteritidis to egg white-based media, with or without egg-white proteins (>10 kDa), under bactericidal conditions (45 °C) was explored by measuring survival and global expression. Surprisingly, the bactericidal activity of egg white at 45 °C was only slightly affected by egg-white proteins indicating that they play a minor role in the bactericidal activity observed. Moreover, egg-white proteins had minimal impact on the global-gene-expression response to egg white such that very similar, major regulatory responses (20% genes affected) were observed both with and without egg-white proteins following 45 min at 45°C. Egg-white proteins caused a significant change in expression for just 64 genes, including the psp and lysozyme-inhibitor responses genes which is suggestive of an early membrane perturbation effect. Such damage was supported by disruption of the proton motive force by egg-white proteins. In summary, the results suggest that low-mass components of egg white are largely responsible for the bactericidal activity of egg white at 45 °C.